SOSIALISASI GRATIFIKASI UNTUK MENGHINDARI TINDAKAN KORUPSI (STUDY KASUS TEMPORAL KEPADA MASYARAKAT KOTA MATARAM) - NI WAYAN INGGRIANI (Universitas Mahasaraswati K. Mataram, 2023)
Study of urban community awareness about gratification and corruption can be done by utilizing the Mataram City Car Free Day event which is held every week. By taking advantage of this event, it is expected to obtain a general picture of the understanding of the people of gratuity and corruption in the city of Mataram. Considering it’s a weekly routine from the City of Mataram, it has the potential to get a lot of visitors who can provide opinions, insights and views on gratuity and corruption. Data collection was carried out by recording the number of visitors, the results of interviews and the number of pamphlets distributed to visitors, and data was analyzed against relevant regulation, especially applicable laws. The study shows that public awareness about gratification and public knowledge about gratuities and corruption is still very limited, including the public still needs regular socialization about the contents of the Gratification and Corruption Law, and needs more specific socialization that discusses the more detailed sections of gratuities and corruption.